Effect of an interprofessional small-group communication skills training incorporating critical incident approaches in an acute care and rehabilitation clinic specialized for spinal cord injury and disorder - Scheel-Sailer, Anke; Eich, Stephanie; Jelmoni, Luca; Lampart, Patricia; Schwitter, Michael; Sigrist-Nix, Diana; Langewitz, Wolf (Frontiers in Rehabilitation Sciences, 2022)
Aim: To investigate the impact of site-specific inter-professional small-group communication skills training (CST) incorporating critical incident approaches to learning on patient satisfaction with communication. Setting: Rehabilitation clinic specialized for spinal cord injury/disorder (SCI/D). Methods: Retrospective observational cohort study design using patient and health-professional self-report data. Data for patient satisfaction with communication was collected in 2014 (existing records) and in each year from 2015 to 2021 (post-program; volunteers) using MECON survey. Results: Fifteen basic (n=161 participants), 16 refresher (n=84) and five short (n=17) CST seminars were conducted. Overall, 262 employees (105 physicians, 63 nurses, 36 physio- and occupational therapists, and 58 others) participated; 92 participants (response rate 37.6%) responded to feedback surveys. They rated the seminars positive concerning the alternation between theory, discussion, and practical exercise in 91.3% and the length of the trainings ideal 80.2%. Post-program patient satisfaction overall increased from 83.1% (confidence interval (CI) 2.6%) to 90% (CI 0.8%; R2 = 0.776; p= 0.004). It was higher in specific communication-related topics: "receiving information" (81.1%, CI 3.1% to 90.2%, CI 1.0%; p= 0.003), "being able to bring in concerns" (83%, CI 1.0% to 90.8%; R2 = 0.707; p= 0.009) and "being treated with respect" (89.4%, CI 2.6% to 94.4%, CI 0.8%; R2 = 0.708; p= 0.004). Practice Implications: Inter-professional CST is feasible and well accepted by professionals from various professional groups. During seven years of continuous training, independent patient ratings of satisfaction with professional communication has improved significantly. Participants attest to the training’s high credibility and usefulness in everyday life.